Genome-wide identification and expression analysis of tomato glycoside hydrolase family 1 β-glucosidase genes in response to abiotic stresses. Issue 1 (31st December 2022) - Wei, Jinpeng; Chen, Qiusen; Lin, Jiaxin; Chen, Fengqiong; Chen, Runan; Liu, Hanlin; Chu, Peiyu; Lu, Zhiyong; Li, Shaozhe; Yu, Gaobo
Abstract: In plants, β-glucosidases (BGLUs) are important glycoside hydrolases involved in several biological phenomena, including the response to stresses via the activation of phytohormones and the release of alpha-hydroxy nitriles to protect against stresses. Due to the importance of BGLUs in plant growth and stress response, genome-wide analyses have been conducted in Arabidopsis and rice, while not in tomato ( Solanum lycopersicum ). In this study, we identified 20 BGLU genes in the tomato that were unevenly distributed on nine chromosomes and divided into five subgroups. There were a variety of plant hormones and stress response cis -elements in the promoter region of the SlBGLU gene, indicating that the BGLU gene may be involved in several aspects of the tomato stress response. SlBGLU gene expression analysis showed that the BGLU gene of tomato was expressed in many tissues, especially in the roots and leaves. Transcriptome data and results of real-time quantitative reverse transcription-polymerase chain reaction showed that most SlBGLU genes could be induced by abscisic acid, chlorothalonil, NaCl and cold (4 °C), especially SlBGLU13 and SlBGLU19, which may be key BGLU genes in response to stress and hormonal stimulation in the tomato. In addition, we constructed a competing endogenous RNA (ceRNA) network, which confers a new direction for studies on the function of SlBGLU genes. These findings not only further clarify the potential function of the BGLU gene family in mediating abiotic stresses in the tomato, but also provide valuable information for the study of functional genomics of the tomato in the future.